Climate security policy coherence and awareness analysis: Guatemala and Central America - Schapendonk, Frans; Scartozzi, Cesare Marco; Madurga Lopez, Ignacio M.; Mohamed, Salma Emad Kadry; Läderach, Peter R.D.; Pacillo, Grazia (2023)
This report analyses the content of Guatemalan and regional-level Central American policy and strategy documents in order to assess the extent and nature of engagement with the climate, peace, and security nexus, as well as the degree to which cross-sectoral and cross-scalar coherence exists between sectors relevant to the nexus. Over 80 regional, national, and sub-national policy documents were assessed using an automated content analysis (ACA) approach, testing for the in-text presence of key variables and proxies representative of thematic engagement and awareness of the nexus, technical components and approaches consistent with the nexus, as well as coordination across sectors and scales. The report finds a lack of awareness and prioritisation of the relationship between climate change and natural resource-related conflict, the potential impacts of climate change on gender-based violence (GBV), and insufficient integration of the climate-related security risks specific vulnerable groups may face in the future. Furthermore, the report identifies that key climate policy instruments within Guatemala - such as the National Climate Change (FONCC) or the Local Climate Change Action Plans - offer important opportunities for the mainstreaming of peace and security considerations into climate action.